The role of physical education teacher creativity in mediating the influence of HRM practices and performance during the COVID-19 pandemic - Muzakki, Abdurrohman; Muammal, Immanuel; Prakoso, Bayu (UIR Press, 2021)
This research was conducted with the aim of analyzing the position of teacher creativity in an effort to mediate the influence of the practice of Human Resource Management (HRM) which can be carried out by schools to improve teacher performance. This type of research is an explanatory research and also uses a quantitative approach. The variables in this research include several aspects such as the practice of implementing HRM, Teacher Creativity, and the performance of Sports Physical Education Teachers. This research was conducted by reaching a number of 102 Sports Physical Education teachers consisting of several levels such as elementary, middle, and high schools in Malang City, Malang Regency and Batu City. Information can be obtained by distributing questionnaires either directly (offline) or online. The analysis of data information was carried out by researchers using SEM-PLS with the WARP PLS 7 application Meanwhile, the results of this research indicate the findings that the practice of HRM does not have a direct influence on the performance of Sports Physical Education Teachers with a significance value of 0.30 and the effect of HR Practice on The performance of sports teachers mediated by teacher creativity has a significance value of <0.001, which means that the teacher's creativity fully mediates the effect of HR practice on the performance of sports teachers.